Analysis of the distribution of plant nutrients in a biogas production system - Johansson, André (2019)
This study examined nutrient flows in a system where 20 farms deliver manure to a biogas plant for digestion, and then receive digestate back. Some other substrates were also anaerobically digested at the plant e.g. slaughter residues. The farms had different types of production: Organic and conventional dairy and conventional pig. The aim was to analyse the re-distribution of plant nutrients this creates. Biogas pro-duction is of interest since it has the potential to reduce the use of fossil fuels and potentially also greenhouse gas emission. The use of digestate as fertilizer has the potential for a more even distribution of plant nutrients across the landscape.